Political environments influenced on the development of libraries- evidences from Jaffna, Sri Lanka - Navaneethakrishnan, S.; Arulanantham, S. (Graduate Studies, University of Kelaniya, 2014)
In this post war era of Sri Lanka, the library professionals occupy in a strategic position in the development of this country and it was felt that this is the opportune time to take serious note on the influence of political environment on the library development of this nation. A review of literature shows that, few numbers of studies have been done to identify the influence of political environment on the development of libraries. Particularly more studies were conducted in African countries. Objective of this study was to identify the significant historical evidences, where the political environments influenced on the development of libraries in Jaffna district of Sri Lanka. Historical events were analyzed in this study based on the descriptive methodology, which involves study, understanding and interpretation of political condition of this district. The findings of this study identified the following evidences. State papers on the Portuguese period had been collected by the Portuguese. Such an archive had destroyed in 1796 by Dutch officials in Jaffna to deprive the information required for efficient administration of British Empire. During British control there is a practice of maintaining and preserving official documents and records pertaining to the judicial and civil administration and this leads origin of archives found in the city of Jaffna. There is evidence of ancient Arian kingdom of Jaffna who had encouraged libraries by providing royal patronage, and evidence is also available for the renovation of a library named ‘Saraswathi Mahal’ which has been destroyed during the many invasions. The destruction of the Jaffna Public Library was the incident which appeared to cause the most distress to the people of Jaffna during the ethnic conflict and political instability in 1981.Restriction of information access occurred during the curfew under the emergency law during the war situation in 1987 to 1996. Libraries were severely affected during the displacement crisis in Jaffna during the period of 1995 to 1996. (317 words
Keywords: Public libraries; Sri Lanka; Development